N-Nitrosodimethylamine Contamination in the Metformin Finished Products - Zmysłowski, Adam; Książek, Iza; Szterk, Arkadiusz (Molecules (Basel, Switzerland), 2020)
A GC–MS/MS method with EI ionization was developed and validated to detect and quantify N-nitrosodimethylamine (NDMA) and seven other nitrosamines in 105 samples of metformin tablets from 13 different manufactures. Good linearity for each compound was demonstrated over the calibration range of 0.5–9.5 ng/mL. The assay for all substances was accurate and precise. NDMA was not detected in the acquired active pharmaceutical ingredient (API); however, NDMA was detected in 64 (85.3%) and 22 (91.7%) of the finished product and prolonged finished product samples, respectively. European Medicines Agency recommends the maximum allowed limit of 0.032 ppm in the metformin products. Hence, 28 finished products and 7 pronged dosage products were found to exceed the acceptable limit of daily intake of NDMA contamination. The implications of our findings for the testing of pharmaceutical products are discussed.